Students’ Perception of Reference Services as Determinant of Library use in Colleges of Agriculture in Oyo State, Nigeria - Odubanjo-Francis Abidemi O. & Adelowo Elizabeth Oluwafunmilayo, Adeyi Olugbenga Ezekiel (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2018)
Descriptive survey design was used to study the students’ perception of reference services as determinant of library use in the Colleges of Agriculture in Oyo State (Federal College of Agriculture, Moor Plantation, Apata, Ibadan [FCAIB] and Oyo State College of Agriculture and Technology, Igboora [OYSCATECH]). The study has four objectives, three research questions and one research hypothesis was tested at 0.05 level of significance. Purposive stratified proportionate random sampling technique and a sampling fraction of fifteen percent (15%) were used to select a sample size of two hundred and eighty-seven (287) students out of the one thousand eight hundred and eighty-five (1885) students in the eight (8) departments that are common to the two Colleges (Population of the study). The response from a well-structured questionnaire administered on the sampled population was analyzed using Statistical Package for Social Science (SPSS). The result of the analyzed data showed positive perception of reference services in OYSCATECH (WX=2.71) and FCAIB (WX= 2.44). The result showed positive correlation between the perception of reference services and use of library in the two colleges of Agriculture in Oyo State FCAIB ( r = 0.311) and OYSCATECH (r = 0.214). The study also identified purposes and frequencies of using the library by the students in the two institutions. The study recommended the use of electronic reference services in order to enhance ease, visibility, relevance and efficiency of reference services in our libraries and more importantly to encourage use of library.